The HITRAN 2008 molecular spectroscopic database - Rothman L. S.; Gordon I. E.; Chris Benner D.; Bernath P. F.; Birk M.; Boudon V.; Brown L. R.; Campargue A.; Chance K.; Coudert L. H.; Dana V.; Devi B. M.; et al. (2009, 2009)
Title screen